Lessons From the Survival of an Extremely Preterm Neonate Despite Challenges in a Country Where Gestational Age of Viability Is 28 Weeks - Elim Kwasi Ahorlu; Andrew Mpagwuni Ziblim; Abdul‐Hanan Saani Inusah; Barbara Swanzy‐Asare; Edith Kissi (Clinical Case Reports)
ABSTRACT Managing extremely preterm neonates with very low birth weight is challenging, especially in Ghana where viability is set at 28 weeks. This case highlights the complexities of neonatal care in low‐resource settings and emphasizes the need for improvement in health systems to revise the age of viability.